Examination of a multi-tiered systems of support tier 2 group intervention at the secondary level - Sellers, Lindsey A. (Kansas State University, 2022)
Adolescence is a time when many changes and challenges occur in an adolescent’s life. It is imperative that schools work to provide learning opportunities and supports for all students. Social emotional learning (SEL) is the process through which social-emotional competence develops. Through SEL, children and youth acquire and effectively apply the knowledge, attitudes and skills necessary to understand and manage emotions, set and achieve positive goals, feel and show empathy for others, establish and maintain positive relationships and make responsible decisions (Weissberg et al., 2015). In order to address and teach social emotional skills, there must be systematic implementation within the school setting. The use of Multi-Tiered Systems of Support (MTSS) is a school-wide, three-tiered approach for providing academic, behavioral and social supports to all students based on their needs and skills (Cook, et. al., 2015, Harlacher, et, al., 2014; Sugai & Horner, 2009; Sugai & Simonsen, 2012). Using the Muli-Tiered System of Supports, student support teams can better align programs to better meet student needs, thus improving student achievement and behavior. The study explored social behavior, academic behavior, and emotional behavior in 9th and 10th grade students from a rural high school in a mid-size Midwestern city. The study population includes 180 participants in a high school using ANCOVA analysis comparisons. The survey administered in the study is the Social, Academic, and Emotional Behavior Risk Screener (SAEBRS) screening tool from Illuminate Education to identify students for participation in a Tier 2 Student Support Group. One hundred Tier 2 identified students participated in a six-session intervention Student Support Group. Sixty-eight identified students did not receive the intervention services. An ANCOVA analysis was conducted to determine the influence of the Tier 2 Group Intervention on students who were identified with risk factors compared to those who did not receive the intervention. The findings for teacher assessment SAEBRS-TRS results did indicate statistical differences for students who participated in the Tier 2 Student Support Group Interventions versus those who were in the comparison group.
Keywords: Support; Multi-tiered; Groups; Intervention